One-dimensional plasmonic excitations in gold-induced superstructures on Si(553): impact of gold coverage and silicon step edge polarization - Hötzel, Fabian; Galden, Nils; Baur, Sebastian; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
Free charge carriers confined to atomic chains such as the gold-induced superstructures on the stepped Si(553) surface enable experimental insight into one-dimensional physics. Embedding into the higher dimensional substrate allows for additional couplings between the free charge carriers and their surroundings, which might modify the one-dimensional characteristics. The gold atom superstructures on Si(553) consist of a parallel arrangement of metallic chains from Au and Si atoms on the terraces and of parallel Si step edges with some of the Si atoms having dangling bonds with one unpaired electron. The metallic chains give rise to localized plasmonic excitations. We have studied these plasmonic resonances with infrared spectroscopy that enables the detection of resonance shifts as small as 1 meV or even less. The plasmonic behavior of the conductive chains of the high- and the low-coverage gold superstructures on Si(553) is investigated at various temperatures and additionally after filling electrons into certain electronic states by placing gold adatoms onto the high-coverage structure. When cooling to 20 K, the strong plasmonic signals of the undoped superstructures become even stronger but shift to lower frequencies, which is attributed to the temperature dependent change of the orientational polarization of the Si dangling bonds. Regarding their plasmonic resonance shifts, the conductive atom chains work just like refractive index sensors.